Crenças e rituais de famílias de pessoas dependentes de alcool: revisão integrativa - Costa, Marceli Karina (2022)
Facilitating and restrictive beliefs influence families in the process of living with and facing the situation of alcohol dependence, in relation to its functionality and treatment. Rituals are resources created and used by families so that they can function and face everyday life. Objective: To identify, in scientific productions, the beliefs and rituals that permeate the experience of the family that lives with alcohol dependents and how they impact the family dynamics. Methodology: Integrative review of national and international literature from 2000 to 2020, in the PubMed/Medline, LILACS, Scopus, Web of Science, CAPES Periodicals, CINAHL, PsycINFO databases, using the PICo strategy, under the guidelines of the document Preferred Reporting Items for Systematic Reviews and Meta-Analysis-extension for scoping reviews (PRISMA-ScR) and theoretical interpretive basis of the Disease Belief Model (CDM). Results: Facilitating beliefs consisted of beliefs of care, hope, cure of the disease and spirituality and religiosity. However, beliefs related to care and religiosity were recognized as both facilitating and restrictive beliefs. The restrictive beliefs involved themes of hopelessness, distancing the alcoholic from and by the family, acceptance and normalization of the alcohol problem, denial of the disease by the family member and belief in care, in which there was a negative influence on alcohol consumption. Regarding family rituals, these were identified in both positive and assertive and negative aspects, that is, they hinder functionality and family dynamics. The rituals that facilitated the functionality and family dynamics involved situations related to the care of the alcohol user, empathic understanding of the family towards the user; the rituals that hampered the functionality of the family consisted of social isolation and exclusion of the member who used alcohol from family life, the consumption of family alcohol recognized as a cultural and transgenerational act; presence of the ritual of silence, of confrontation, religious; ritual of moving house due to embarrassing situations and unstable routine rituals. Final considerations: The same belief can be both facilitating and restrictive for different families in the universe of alcohol dependence, depending on several factors, which will influence the perception and feelings generated by the family unit so that it can take behavioral action in the face of adverse or challenging situations, resonating in family dynamics and functioning.